CALCULATION OF NORMAL CONTACT STRESS IN THE DEFORMATION FOCUS AT ROLLING OF STRIPS - Yavtushenko , Aleksander; Ptotsenko , Viktor; Bondarenko , Yuliya (Scientific Journal "Metallurgy", 2020)
Possibility of application of programmatic complex «MathCAD Prime 5» is considered for the calculations of normal pin tensions in the heart of deformation at the cold rolling of stripes. The algorithm, the block diagram and the computer program of calculation the normal contact pressure are developed when rolling of strips on reversive rolling mill 1680 of PSC «Zaporizhstal ». Epures and a comparative analysis of the formulas used to calculate the normal contact stresses in the deformation zone are constructed. Settlement data, received in «MathCAD Prime 5», coincide with literary data that has practical value both for educational process and for research and design work. Calculations of normal pin tensions at rolling thin stripes can be executed with the use of Tselikov formula. With purpose of comparizon of results of calculation of normal pin tensions on all formulas in accordance with the real modes of deformations on the reversible mill 1680 the «Metalurgical conbine Zaporozhstal» was worked out algorithm and program of calculations in programmatic complex «MathCAD Prime 5». For determination of size of pressure the algorithm of calculations is worked out in the arbitrary crossing of cell of deformation. The cell of deformation is broken up on the row of crossing (from 0 to k). In every crossing a current height of stripe determines and compared to the height by stripe in the neutral crossing hn. A height hn is determined on condition of equality of pressures in this crossing from the side of area of lag and passing. Calculations executed in a programmatic complex «MathCAD Prime 5». The cell of deformation was broken up on a 20 crossing (indexes k, i) and in every crossing calculated normal pin tensions of P0 for the area of lag, P1 – for the area of passing. Comparison of areas of epured of normal pin tensions got on the simplified formulas and by more exact Tselikov equations shows that these areas almost fully coincide: their maximal deterrence does not exceed 5 %. Consequently the simplified formulas are equivalent on exactness of deformation of size of normal pin tensions. An algorithm, flow-chart and computer program of calculation of normal pin tensions are worked out in the cell of deformation at the cold rolling stripe on the reversive rolling mill 1680 of PSC «Zaporizhstal » by means of programmatic complex «MathCAD Prime 5». The results of calculations coincide with literary data. Epures are built and the comparative analysis of formulas which use for the calculations of normal pin tensions in the cell of deformation is executed. It is shown that the most reliable cam be got at the use of formulas which take into account treason of the forced limit of fluidity in the cell of deformation.